Adenomyosis: Difficult to Diagnose, and Difficult to Treat. Issue 2 (2001) - Wood, C.
Abstract : Drug therapy may be effective in controlling symptoms but the frequent coexistence of endometriosis and the lack of controlled studies make their efficacy difficult to quantify. Danazol IUD has been shown to reduce symptoms. Conservative surgery involving endomyometrial ablation, laparoscopic myometrial electrocoagulation or excision has proven to be effective in more than 50% of patients, although follow up has been restricted to three years. Arterial uterine artery embolization is a new technique which may be tried before considering hysterectomy. Hysterectomy may still be necessary in severe cases of adenomyosis.